2013
DOI: 10.3109/10826084.2013.808540
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality as a Change Mechanism in 12-Step Programs: A Replication, Extension, and Refinement

Abstract: This National Institutes of Health funded study investigated spiritual growth as a change mechanism in 12-step programs. A total of 130 people, early 12-step affiliates with limited Alcoholics Anonymous (AA) histories, were recruited from 2007 to 2008 from AA, treatment, and community centers in a Southwestern city in the United States. A majority of the sample was alcohol dependent. Participants were interviewed at baseline and at 3, 6, and 9 months. Lagged General Linear Modeling analyses indicated that spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 41 publications
3
36
0
3
Order By: Relevance
“…Next, our findings provide support for the hypotheses that participants with higher scores on spirituality would have a lower risk for alcohol consumption and agree with prior research (Kelly et al 2011; Tonigan et al 2013). It is possible that presence of higher spirituality provides ways of living life that are less compatible with alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Next, our findings provide support for the hypotheses that participants with higher scores on spirituality would have a lower risk for alcohol consumption and agree with prior research (Kelly et al 2011; Tonigan et al 2013). It is possible that presence of higher spirituality provides ways of living life that are less compatible with alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al (2014) found that increased daily spiritual experiences score was associated with greater likelihood of abstinence in a residential treatment program for adolescents. Other studies examined the role of spirituality in 12-step programs and suggested that spiritual growth predicted reduced drinking (Tonigan et al 2013) and that better alcohol outcomes for Alcoholics Anonymous members were partially mediated by increased spirituality (Kelly et al 2011). Still, to our knowledge, no study has examined the association between alcohol use and spiritual involvement in general population in Ukraine.…”
Section: Risk Factors For Alcohol Usementioning
confidence: 99%
“…This is a relevant finding because spirituality is an important part of the 12-step model. In fact, spiritual growth is thought to be a change mechanism specific to 12-step programs, one study demonstrating that changes in reported spiritual beliefs predicted better alcohol use outcomes during early 12-step affiliation (Tonigan, Reyes, & McCrady, 2013). Spirituality may play a larger role in the overall recovery efforts of African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Using formal mediational tests, some of these studies have demonstrated first that frequency of AA meeting attendance predicted increased spiritual practices, and that such gains predicted later decreases in alcohol consumption (usually abstinence) (Kelly et al, 2012; Krentzman et al, 2013; Tonigan et al, 2013; Zemore, 2007). Our findings from the mediation analysis and lagged analysis suggest that spiritual gains may indeed predict later reductions in depressive symptom counts among AA members, even though engagement in spiritual practices are not described by AA attendance frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many theorists regard the experience of negative affect to be a primary precipitant for alcohol relapse (e.g., Marlatt and Donovan, 2007), including AA doctrine. In this regard, recent attention has focused on formally testing how reductions in different aspects of negative affect among AA members, including depression, may account for AA-related benefit (Kelly et al, 2010; Tonigan et al, 2013; Worley et al, 2012). Third, 12-step treatments [e.g.…”
Section: Introductionmentioning
confidence: 99%